2004
DOI: 10.1007/s00429-003-0368-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride-induced alterations of enamel structure: an experimental study in the miniature pig

Abstract: We studied the structural changes in the enamel of mandibular third molars of miniature pigs administered a daily oral dose of 2 mg NaF (approximately 0.9 mg of fluoride) per kg body weight (added to the feed) for 1 year. The treatment period covered most of the secretory stage and the entire post-secretory stage of amelogenesis of the M(3). The enamel of the molars from the fluoride-fed pigs appeared opaque and chalky, and the erupted portions were stained brown. The underlying histopathological change was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 43 publications
5
54
0
Order By: Relevance
“…Mineralization defects in rat incisor maturation-stage enamel can develop during prolonged exposure to fluoridated drinking water at levels as low as 9-10 ppm fluoride (Shinoda, 1975;Angmar-Månsson et al, 1976), and are characterized by the development of a generalized hypomineralized porous subsurface area along the entire crown enamel (Fig. 3a) (Shinoda, 1975;Angmar-Månsson et al, 1976;Whitford, 1982, 1984;Richards et al, 1992;Kierdorf et al, 2004). This type of defect correlates to the porous white opacities seen clinically.…”
Section: Maturation Ameloblastsmentioning
confidence: 98%
See 2 more Smart Citations
“…Mineralization defects in rat incisor maturation-stage enamel can develop during prolonged exposure to fluoridated drinking water at levels as low as 9-10 ppm fluoride (Shinoda, 1975;Angmar-Månsson et al, 1976), and are characterized by the development of a generalized hypomineralized porous subsurface area along the entire crown enamel (Fig. 3a) (Shinoda, 1975;Angmar-Månsson et al, 1976;Whitford, 1982, 1984;Richards et al, 1992;Kierdorf et al, 2004). This type of defect correlates to the porous white opacities seen clinically.…”
Section: Maturation Ameloblastsmentioning
confidence: 98%
“…Whether such lesions erupt as pits (Kierdorf et al, 2004), or develop into pits post-eruptively by mechanical damage of the surface layer that covers the porous subsurface defect (Fejerskov et al, 1994), remains to be investigated. Studies in sheep suggest that both options are possible (Suckling and Thurley, 1984).…”
Section: Late-secretory Transitional Ameloblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of different types of hypoplastic defects denotes a marked impairment of secretory ameloblast function. The grossly enhanced incremental lines in the enamel indicate the location of the surface of the forming enamel at the time of a severe impact on the secretory ameloblasts that caused a permanent or transient cessation of matrix secretion (Kierdorf et al 2000(Kierdorf et al , 2004. Externally visible hypoplastic defects formed when groups of ameloblasts failed to resume their normal secretory function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in domestic pigs and wild boar also suggested that histological analysis of developmental defects of enamel enables an assessment of the duration and intensity of stress episodes of different nature that affected enamel formation (Kierdorf et al, 2004(Kierdorf et al, , 2005Witzel et al, 2006).…”
Section: Introductionmentioning
confidence: 97%